2008
DOI: 10.1161/circulationaha.107.739227
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Components of the Circadian Clock Regulate Thrombogenesis In Vivo

Abstract: Background-Myocardial infarction, stroke, and sudden death undergo diurnal variation. Although genes relevant to hemostasis and vascular integrity undergo circadian oscillation, the role of the molecular clock in thrombotic events remains to be established. Methods and Results-A diurnal variation in the time to thrombotic vascular occlusion (TTVO) subsequent to a photochemical injury was observed in wild-type mice: TTVO varied from 24.6Ϯ2.7 minutes at zeitgeber time (ZT) 2 to 40.3Ϯ4.3 minutes at ZT8, 24.3Ϯ2.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 50 publications
4
129
0
1
Order By: Relevance
“…Recently, several genetic models in which molecular clocks were modulated in a cell type-specific manner have been developed to account for the tissue-or organ-specific regulation and function of clock genes (29)(30)(31). In this context, our adrenal-specific BMAL1 knockdown mice provide a useful system for testing the unique role of the adrenal peripheral clock in harmonizing and maintaining the circadian timing system, because GC has been proposed to be a Zeitgeber for peripheral oscillators (4).…”
Section: Role Of the Adrenal Oscillator In Harmonizing The Circadian mentioning
confidence: 99%
“…Recently, several genetic models in which molecular clocks were modulated in a cell type-specific manner have been developed to account for the tissue-or organ-specific regulation and function of clock genes (29)(30)(31). In this context, our adrenal-specific BMAL1 knockdown mice provide a useful system for testing the unique role of the adrenal peripheral clock in harmonizing and maintaining the circadian timing system, because GC has been proposed to be a Zeitgeber for peripheral oscillators (4).…”
Section: Role Of the Adrenal Oscillator In Harmonizing The Circadian mentioning
confidence: 99%
“…In blood vessels, regulation of vascular function and tone has shown to be regulated by circadian rhythms. For example, deletion of Bmal1 specifi cally in vascular endothelium leads to a reduction of blood pressure during the active phase of the day and increased heart rate throughout the 24-h cycle (Westgate et al 2008 ). The ability of endothelial cells from Per2 mutant mice to proliferate and form vascular networks is substantially reduced, which is marked by increased senescence of the cells (Wang et al 2008 ).…”
Section: Transgenic Animals Provide Novel Insights To Better Understamentioning
confidence: 99%
“…In vivo, Per2 mutant mice show decreased angiogenesis, as blood fl ow is impaired and combined with reduced recovery in response to ischemia characterized by a smaller increase in vessel formation. Lastly, Westgate et al ( 2008 ) showed that the time to thrombotic vascular occlusion in response to a photochemical injury displays diurnal variation. Platelet aggregation factors, plasminogen activator inhibitor and tissue plasminogen activator, produced by the vascular endothelium show diurnal variability throughout the day/night cycle.…”
Section: Transgenic Animals Provide Novel Insights To Better Understamentioning
confidence: 99%
“…24 In contrast, the endothelial-specific deletion of Bmal1 did not affect the variation in BP, suggesting that the peripheral clock in endothelial cells does not solely induce diurnal BP rhythm. 41 A genetic association study showed that a single-nucleotide polymorphism within the bmal1 promoter is associated with hypertension and type II diabetes, 42 providing support that the molecular clock is involved in the pathogenesis of metabolic disorders. Recent evidence supported the contribution of peroxisome proliferator-activated receptor-g (PPARg) in the clock system.…”
Section: Bp/hypertension and The Molecular Clockmentioning
confidence: 99%
“…70 Oishi et al 71 showed that a ketogenic diet induces the phase shift of peripheral clock gene expression including PAI-1, suggesting that PAI-1 expression is regulated by the peripheral clock. Westgate et al 41 studied the susceptibility to thrombotic events using a mouse photochemical injury model and observed a diurnal variation in thrombogenicity in this in vivo model. CLOCK mut mice have lost this dynamic variation.…”
Section: Ami and The Circadian Clockmentioning
confidence: 99%